2020
DOI: 10.1016/j.jtemb.2020.126520
|View full text |Cite
|
Sign up to set email alerts
|

Altered clearance of beta-amyloid from the cerebrospinal fluid following subchronic lead exposure in rats: Roles of RAGE and LRP1 in the choroid plexus

Abstract: Formation of amyloid plaques is the hallmark of Alzheimer's disease. Our early studies show that lead (Pb) exposure in PDAPP transgenic mice increases β-amyloid (Aβ) levels in the cerebrospinal fluid (CSF) and hippocampus, leading to the formation of amyloid plaques in mouse brain. Aβ in the CSF is regulated by the blood-CSF barrier (BCB) in the choroid plexus. However, the questions as to whether and how Pb exposure affected the influx and efflux of Aβ in BCB remained unknown. This study was conducted to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Therefore, we investigated the deposition of Aβ 1-40 in choroid plexus and microvessels following lead exposure and we observed that lead treatment significantly promoted the deposition of Aβ1-40 in these two vascularized structures in the brain. In line with our study, recently, Shen et al reported that the expression of Aβ in the choroid plexus was significantly upregulated in leadtreated group [31]. Furthermore, the expression of ABCB1, LRP-1, and RAGE, three major receptors responsible for Aβ transportation, was measured.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we investigated the deposition of Aβ 1-40 in choroid plexus and microvessels following lead exposure and we observed that lead treatment significantly promoted the deposition of Aβ1-40 in these two vascularized structures in the brain. In line with our study, recently, Shen et al reported that the expression of Aβ in the choroid plexus was significantly upregulated in leadtreated group [31]. Furthermore, the expression of ABCB1, LRP-1, and RAGE, three major receptors responsible for Aβ transportation, was measured.…”
Section: Discussionsupporting
confidence: 91%
“…A longitudinal incision was made in the scalp to expose the surface of the skull. A cranial burr hole (1 mm) was drilled into the skull of the right hemisphere with the following coordinates: 0.3 mm posterior to bregma and 1.0 mm lateral to the midline ( Paxinos and Franklin, 2001 ; Shen et al, 2017 , 2020 ). Next, a stainless steel cannula (RWD, Shenzhen, China) was embedded at 3.2 mm vertical from the skull surface ( Young et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…ICV injection of drug solutions was performed manually at a rate of 0.5 μL/min ( Dore et al, 2017 ) in freely moving animals through the cannula, which was connected to a 5 μL Hamilton microsyringe (Reno, NV, United States), and the injection cannula was kept in situ for an additional 3 min to avoid reflux of the solution along the injector track. The ICV injection technique is well established in this lab and was used in our previous studies ( Shen et al, 2017 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex equilibrium between fluid drainage and Aβ deposition observed at the perivascular level in AD is also detected within the ChP. Aβ transporter proteins are expressed at both the BBB and BCSFB contributing to a coordinated clearance of Aβ into the peripheral circulation ( 123 , 360 , 361 ). Underscoring disease-specific defects in barrier transport mechanisms, ChP tissue from AD patients shows substantial deposition of Aβ peptide and increased oxidative stress ( 362 ).…”
Section: Myeloid Dwellers and Trespassers At Cns Interfaces In Neurodmentioning
confidence: 99%